Analysis of Mukakuning and Duriangkang Reservoir’s Capacity to Fulfill The Raw Water Demand of Batam City - Willy Aulia; Robertus Wahyudi Triweko; Bambang Adi Riyanto; Wanny K Adidarma; Doddi Yudianto (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2020)
Batam City is the economic center of Riau Province with a predicted population of 1.8 million people in 2025. To support economic development, Batam City needs a reliable supply of raw water. Mukakuning and Duriangkang reservoirs, which are cascade reservoirs, are the largest contributors to raw water supply in Batam City. This study aims to determine the maximum capacity of the two reservoirs to meet current and future raw water demand. Discharge in the watershed is calculated using daily HEC-HMS model calibrated using Duriangkang Reservoir water level data. The storage of Mukakuning and Duriangkang Reservoir are 6.3 and 106.1 million m3 respectively, equivalent to 39% and 77% of the runoff volume of each watershed, classifying the two reservoirs in the multi-year category. Using current operation, the two reservoirs can supply up to 3.24 m3/s at 100% reliability, compared to existing capacity of 3.1 m3/s. The water loss is dominated by evaporation which reaches 32.6 million m3/year while spilled water is only 8.3 million m3/year. At 95% reliability, the reservoirs are almost at maximum capacity and able to supply 4.03 m3/s of raw water with the spilled water is only 0.4 million m3/year. Efforts to increase capacity by increasing normal water levels are not effective and lead to dam overtopping in PMF condition. More effective way to increase water supply can be obtained by changing operating patterns. If the reservoir is in dry condition, determined by predicted SPI, the water supply is limited so that the discharge can be utilized for a longer period.